2020
DOI: 10.1002/glia.23777
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectory of oligodendrocyte progenitor cells in the human brain revealed by single cell RNA sequencing

Abstract: Characterizing the developmental trajectory of oligodendrocyte progenitor cells (OPC) is of great interest given the importance of these cells in the remyelination process. However, studies of human OPC development remain limited by the availability of whole cell samples and material that encompasses a wide age range, including time of peak myelination. In this study, we apply single cell RNA sequencing to viable whole cells across the age span and link transcriptomic signatures of oligodendrocyte‐lineage cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 56 publications
3
41
3
Order By: Relevance
“…This indicates that based on their transcription profiles, adult OPCs look more like myelinating OLGs than neonatal OPCs. In line with this, a recent study that compared human OLGs in development and aging revealed that based on gene expression, a distinction can be made between OPCs from pediatric and adult brains [55]. More specifically, gene ontology annotations enriched in OPCs in the pediatric human brain are related to OLG differentiation, extracellular matrix (ECM) metabolism, axon guidance and cholesterol transport, while gene ontology annotations enriched in OPCs in the adult human brain are related to regulation of cell projections, regulation of molecular transport, and superoxide metabolism [55].…”
Section: Oligodendroglial Lineage Cellsmentioning
confidence: 76%
See 2 more Smart Citations
“…This indicates that based on their transcription profiles, adult OPCs look more like myelinating OLGs than neonatal OPCs. In line with this, a recent study that compared human OLGs in development and aging revealed that based on gene expression, a distinction can be made between OPCs from pediatric and adult brains [55]. More specifically, gene ontology annotations enriched in OPCs in the pediatric human brain are related to OLG differentiation, extracellular matrix (ECM) metabolism, axon guidance and cholesterol transport, while gene ontology annotations enriched in OPCs in the adult human brain are related to regulation of cell projections, regulation of molecular transport, and superoxide metabolism [55].…”
Section: Oligodendroglial Lineage Cellsmentioning
confidence: 76%
“…In line with this, a recent study that compared human OLGs in development and aging revealed that based on gene expression, a distinction can be made between OPCs from pediatric and adult brains [55]. More specifically, gene ontology annotations enriched in OPCs in the pediatric human brain are related to OLG differentiation, extracellular matrix (ECM) metabolism, axon guidance and cholesterol transport, while gene ontology annotations enriched in OPCs in the adult human brain are related to regulation of cell projections, regulation of molecular transport, and superoxide metabolism [55]. In addition, rodent adult OPCs in the aged CNS have increased DNA damage and decreased metabolic function and fail to respond to differentiation signals both in vitro and in vivo [56].…”
Section: Oligodendroglial Lineage Cellsmentioning
confidence: 76%
See 1 more Smart Citation
“…Excitingly, recent sequencing data from human Alzheimer's disease patients and healthy controls demonstrated that healthy controls have three subpopulations of OPCs, and that one of these populations expressed high levels of Clusterin, one of the genes we identified as significantly upregulated in OPC1 59 . Additionally, single-cell sequencing data from human patients at fetal, adolescent, and adult timepoints reveal multiple transcriptionally distinct populations of oligo-lineage cells that largely clustered based on the age of the patient 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Oligodendrocyte lineage cells are the actual suppliers of myelin, which was for a long term described as their only function as a pool of cells. However, high-resolution transcriptomics changed this passive view into a dynamic view, where oligodendrocyte lineage cells display heterogeneity across brain regions (Marques et al, 2016), throughout development (Perlman et al, 2020) and during the course of MS pathology (Jäkel et al, 2019;Schirmer et al, 2019;Yeung et al, 2019). As an example, Yeung et al (2019) identified subsets of disease-specific oligodendrocyte lineage cells in EAE mice.…”
Section: In Situ Hybridization Assaysmentioning
confidence: 99%